Teacher Collaboration in Designing Context-Based Numeracy Tasks - Yurizka Melia Sari; Endah Budi Rahaju; Abdul Haris Rosyidi; Nina Rinda Prihartiwi; Heri Purnomo; Taszkia Aulia Putri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
This study investigates the individual and collaborative designs of context-based numeracy tasks developed by mathematics teachers employing three different contexts, namely, Islamic inheritance law, population census, and genetics. The tasks were designed at different levels of knowing, applying, and reasoning. The obtained data were analyzed using PISA’s contextual framework and Indonesia’s cognitive taxonomy to evaluate task solvability, context type, context level, and cognitive demand. The results show significant differences: most individual designs remained at the knowing level (88.23%), had first-order contexts (88.23%), and had 19.05% of tasks that could not be solved due to insufficient information. Collaborative designs eliminated all tasks that could not be solved, increased the number of reasoning-level tasks from 7.84% to 24.39%, and removed all zero-order context levels. Both preferred social settings (52%), but collaborative designs showed more integration. For example, context-based numeracy problems created individually ask students to determine the percentage of Generation Z. In contrast, group-created problems ask them to analyze the impact of demographics on planning. These findings demonstrate the importance of teacher collaboration in increasing the authenticity and complexity of learning activities. Systematic collaboration frameworks should be incorporated into teacher professional development programs.